IMPLEMENTASI CASE-BASED REASONING UNTUK SISTEM TANYA JAWAB PENYAKIT PADA ANJING - Andre Raymond; Viny Christanti Mawardi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
This debriefing question answering system using Case Base Reasoning algorithm. Case Base Reasoning is an algorithm to solve new problems by comparing the old problems or solve new problems by providing answers from a document.In this system uses several methods to process the document as an information / knowledge that makes the system increasingly relevant in answering the question. The method used is the Modified K-Nearest Neighbour, Vector Space Model and Paragraph Based Passage. M-KNN method is used to facilitate in classifying diseases in dogs, VSM method is used to search for relevant documents that match the query. then to provide answers to relevant documents obtained by the system used method Based Paragraph Passage. This level of accuracy obtained from this exchange system using training data 228 is equal to 92% with a value of k = 3.